Cooperative Transmission for Security Enhancement in Clustered Wireless Sensor Networks - Weiwei Yang; Songqing Wang; Xiaoming Xu (International Journal of Distributed Sensor Networks)
We study opportunistic decode-and-forward relaying transmission in cooperative cluster-based wireless sensor networks (WSNs) with secrecy constraints, where a passive eavesdropper may overhear the source message. To deal with this problem, we consider the novel opportunistic relay section cooperative transmission for the cluster configuration of WSNs. The system performance in terms of the secrecy outage probability and the probability of nonzero secrecy capacity are analyzed and the exact closed-form expressions are derived over Rayleigh fading channels. Furthermore, we derive the asymptotic secrecy outage probability which accurately reveals the secrecy diversity order. Finally, numerical results are presented to verify the theoretical analysis and depict that node cooperation has a great potential to enhance physical layer security against eavesdropping.